Gambaran Pengetahuan dan Sikap Ibu Hamil terhadap Konsumsi Rambutan untuk Mencegah Anemia Pada Ibu Hamil - Sinulingga, Selpyani; Patriani, Sirly (3031-8572, 2023)
The Prevalence of anaemia in pregnant women worldwide has declined of 4.5 % over the past 19 years, while in Indonesia in 2019 the incidence of anemia among pregnant mothers has increased by 4.2 % from 2015. Riskesdas 2018 results show that 8.9% of pregnant women in Indonesia have anemia. Rambutan is one of the tropical plants that is rich in nutrients, rambutan contains vitamin C including potassium, magnesium, zinc, sodium, niacin, iron and protein. The iron can increase the amount of oxygen in the body that can help alleviate the symptoms of dizziness and fainting caused by iron deficiency or anaemia in pregnant women. The study was conducted in September 2022 until August 2023 at the PMB Putri Dewi. The aim of this study is to find out the picture of knowledge and attitude of pregnant mothers to consumption of rambutan to prevent anemia in pregnant women. This research is quantitative with a descriptive approach. Data collection is done with a questionnaire. The population is all pregnant mothers who are PMB Putri Dewi which numbered 40 people with samples according to the inclusion criteria of as many as 30 people. Data analysis is done univariately. The results of the study showed that the majority of pregnant mothers have good knowledge, but the vast majority still have a negative attitude to the consumption of rambutan during pregnancy. From the results of this study, it is expected that health workers and obstetric service providers should be more active in educating the public about the benefits of rambutan consumption to prevent anaemia in pregnant mothers.Â